2018
DOI: 10.2147/cmar.s174409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and analysis of prognostic values in nonsmoking females with non-small cell lung carcinoma by bioinformatics analyses

Abstract: BackgroundThis study was performed to identify disease-related genes and analyze prognostic values in nonsmoking females with non-small cell lung carcinoma (NSCLC).Materials and methodsGene expression profile GSE19804 was downloaded from the Gene Expression Omnibus (GEO) database and analyzed by using GEO2R. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes were used for the functional and pathway enrichment analysis. Then, the Search Tool for the Retrieval of Interacting Genes, Cytoscape, and Molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…An abnormal cell cycle may lead to the occurrence of a variety of different types of tumor, such as hepatocellular carcinoma (33,34), breast cancer (35), pancreatic cancer (36), ovarian cancer (37) and NSCLC in non-smoking females (38). Wang et al (39) used different microarray expression profiles in their study of primitive neuro-ectodermal tumors, and revealed the same four pathways that were identified in the present study, and several of the same genes in the modules that they identified as being important.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal cell cycle may lead to the occurrence of a variety of different types of tumor, such as hepatocellular carcinoma (33,34), breast cancer (35), pancreatic cancer (36), ovarian cancer (37) and NSCLC in non-smoking females (38). Wang et al (39) used different microarray expression profiles in their study of primitive neuro-ectodermal tumors, and revealed the same four pathways that were identified in the present study, and several of the same genes in the modules that they identified as being important.…”
Section: Discussionmentioning
confidence: 99%
“…Another of our candidate prognostic signature gene, KIF20A , has also been reported to be strongly expressed in nasopharyngeal carcinoma (NPC) (49), NSCLC (14,50,51), HCC (52), cervical cancer (53), glioma (54), OC (55) and clear cell renal cell carcinoma (ccRCC) (56). Furthermore, a high expression of KIF20A in these types of cancer has also been shown to be associated with an increased risk of an unfavorable prognosis (14,4953,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignant tumors in the world, and it has become the first cause of death in malignant tumors in urban population in China (Yang et al., 2018). Non-small cell lung cancer (NSCLC) as the main type of lung cancer accounts for about 80% of all cases compared with small cell carcinoma and about 75% of patients are already in the advanced stage (Boolell et al., 2015).…”
Section: Introductionmentioning
confidence: 99%